Self-Reflection: Early Detection and Anemia Education Program for Adolescent Girls Based on Self-Screening and Micro-Nutrition Training at SMK Islam PERTI Jakarta: Penelitian - Nurharlinah; Karyatian; Mia Atlantic; Putri Nathalia; Khanza Aurelia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Anemia in adolescent girls is one of the public health problems that still has a high prevalence in Indonesia. This condition is generally caused by low iron intake, lack of knowledge about micronutrients, and minimal awareness to detect early symptoms of anemia. Anemia that is not treated properly can have serious impacts on the physical, cognitive, and productivity development of adolescents, including decreased academic achievement and increased risk of reproductive health complications in the future.In response to these conditions, a community service program entitled “Cermin Diri” was implemented with the aim of increasing awareness, early detection skills, and understanding of micronutrients among adolescent girls through an educational and participatory approach. This program was implemented at SMK Islam PERTI Jakarta by involving grade X and XI female students as the main participants. The implementation method included interactive educational sessions on anemia and balanced nutrition, training in the use of simple self-screening tools for independent anemia detection, and group discussions to strengthen understanding and commitment to a healthy lifestyle.The results of the activity showed an increase in participants' knowledge about anemia and micronutrients, as well as growing awareness of the importance of early detection and improving diet. Participants also showed enthusiasm in using the self-screening tool and expressed a commitment to applying the knowledge gained in everyday life. This program shows great potential as an effective health education model that can be replicated in other schools to prevent anemia in adolescent girls.